2019
DOI: 10.3390/biom9050185
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Acetylation Mediates Bisphenol A Effects on the Microtubule Arrays of Allium cepa and Triticum turgidum

Abstract: The effects of bisphenol A (BPA), a prevalent endocrine disruptor, on both interphase and mitotic microtubule array organization was examined by immunofluorescence microscopy in meristematic root cells of Triticum turgidum (durum wheat) and Allium cepa (onion). In interphase cells of A. cepa, BPA treatment resulted in substitution of cortical microtubules by annular/spiral tubulin structures, while in T. turgidum BPA induced cortical microtubule fragmentation. Immunolocalization of acetylated α-tubulin reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Based on these findings, our results suggest that BPA reduces meristem size and thus root length by inhibiting cell division through accumulating auxin in the meristem. However, it is also possible that BPA directly inhibits cell division since BPA disrupts microtubule arrays in Pisum sativa, the gymnosperm Abies cephalonica, Triticum turgidum (durum wheat), and Allium cepa (onion) (Adamakis et al, 2019(Adamakis et al, , 2016(Adamakis et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, our results suggest that BPA reduces meristem size and thus root length by inhibiting cell division through accumulating auxin in the meristem. However, it is also possible that BPA directly inhibits cell division since BPA disrupts microtubule arrays in Pisum sativa, the gymnosperm Abies cephalonica, Triticum turgidum (durum wheat), and Allium cepa (onion) (Adamakis et al, 2019(Adamakis et al, , 2016(Adamakis et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of BPA (over 30 µM) inhibited plant growth by enhancing reactive oxygen species and lipid peroxidation in Arabidopsis (Ali et al, 2017) and soybean (Zhang et al, 2016). It was also reported that approximately 50-100 ppm BPA disrupted microtubule arrays, thereby inhibiting cell division in pea (Pisum sativum L.), the gymnosperm Abies cephalonica, Triticum turgidum (durum wheat) and Allium cepa (onion) (Adamakis et al, 2019(Adamakis et al, , 2016(Adamakis et al, , 2013. In addition, 5-10 ppm BPA inhibited pollen tube growth by decreasing the deposition of cell wall components through disrupting Ca 2+ gradients and actin filaments in Picea meyeri (Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Detached leaves of A. thaliana maintained in Petri dishes on filter paper soaked with distilled water were considered as controls. Four to five leaves per experiment were treated with aqueous 50 and 100 mg L −1 (0.2 and 0.4 mM) BPA solutions, prepared from a stock solution of 200 mg L −1 at 21.5°C, pH 7.0 ( Staples et al., 1998 ; Adamakis et al., 2013 ; Adamakis et al., 2019 ), soaked on filter paper in Petri dishes, for 6, 12 and 24 h. Each treatment has been done in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Although plants can absorb and metabolize BPA, at the same time BPA could deteriorate their cellular/physiological status ( Zhang et al., 2017 ). It has been shown that experimentally applied concentrations of BPA (mg/L) negatively affected the growth of many important crops, e.g., soybean ( Qui et al., 2013 ; Zhang et al., 2016 ; Jiao et al., 2017 ; Li X. et al., 2018 ; Zhang et al., 2018 ; Xiao et al., 2019 ), pea ( Adamakis et al., 2013 ), wheat ( Adamakis et al., 2019 ), maize ( Stavropoulou et al., 2018 ), rice ( Ali et al., 2016 ), cucumber ( Li Y. T. et al., 2018 ) and onion ( Adamakis et al., 2019 ); also of non-cultivated plants such as the Cephalonian fir ( Adamakis et al., 2016 ) and the model plant Arabidopsis thaliana ( Pan et al., 2013 ; Tian et al., 2014 ; Frejd et al., 2016 ; Ali et al., 2017 ; Rapala et al., 2017 ; Bahmani et al., 2020 ). Growth reduction effects have interestingly been found to occur also after environmentally relevant concentrations (μg/L) applied on cultivated crops, e.g., cabbage and tomato ( Staples et al., 2010 ), native plants such as oat ( Staples et al., 2010 ) and seagrasses ( Adamakis et al., 2018 ; Malea et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation